2015
DOI: 10.1159/000369392
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Growth Hormone Deficiency in a Pediatric Cohort

Abstract: Background/Aims: Controversies still exist regarding the evaluation of growth hormone deficiency (GHD) in childhood at the end of growth. The aim of this study was to describe the natural history of GHD in a pediatric cohort. Methods: This is a retrospective study of a cohort of pediatric patients with GHD. Cases of acquired GHD were excluded. Univariate logistic regression was used to identify predictors of GHD persisting into adulthood. Results: Among 63 identified patients, 47 (75%) had partial GHD at diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…More than half of the patients (n = 13/24) had normal GH secretion after treatment was discontinued. This finding is similar to that of a previous study that reported that 56% of the patients had normal GH secretion after reaching FAH [ 27 ]. In contrast, patients with MPHD are likely to have persistent GHD compared with those with isolated GHD; this finding is similar to that reported by Thomas et al [ 21 ], who demonstrated that 15% of the isolated GHD cases were persistent GHD cases.…”
Section: Discussionsupporting
confidence: 92%
“…More than half of the patients (n = 13/24) had normal GH secretion after treatment was discontinued. This finding is similar to that of a previous study that reported that 56% of the patients had normal GH secretion after reaching FAH [ 27 ]. In contrast, patients with MPHD are likely to have persistent GHD compared with those with isolated GHD; this finding is similar to that reported by Thomas et al [ 21 ], who demonstrated that 15% of the isolated GHD cases were persistent GHD cases.…”
Section: Discussionsupporting
confidence: 92%
“…Re-evaluation of the GH status has shown that GHD is permanent in patients with CPHD, acquired hypothalamic-pituitary lesions, pituitary hypoplasia, pituitary stalk agenesis and posterior pituitary ectopia. On the contrary, a high proportion of children with isolated GHD and no pituitary abnormalities show a different percentage of normalization of GH secretion, ranging from 12.5% to 95% [98][99][100][101]. Our recently unpublished results showed that, at the time of re-testing, 82.1% of severe GHD and 82.4% of partial GHD patients showed transient GHD.…”
Section: Gh Therapy In Transition Agementioning
confidence: 75%
“…Treatment with somatropin has been associated with improvement in metrics of final height, depression, behavioral issues, and psychosocial evaluations. [7][8][9] In a majority of cases, patients may not require somatropin therapy into adulthood 10 ; however, some patients will require treatment into adulthood. 2 Optimal outcomes in final adult height from somatropin treatment are usually achieved when patients are started early, before age 9 years, 11 and are highly adherent to treatment, defined in Cutfield et al as missing no more than 1 dose per week.…”
Section: What This Study Addsmentioning
confidence: 99%